Interaction between a nano-formulation of atrazine and rhizosphere bacterial communities: Atrazine degradation and bacterial community alterations - Zhai, Yujia; Abdolahpur Monikh, Fazel; Wu, Juan; Grillo, Renato [UNESP]; Arenas-Lago, Daniel; Darbha, Gopala Krishna; Vijver, Martina G.; Peijnenburg, Willie J. G. M. (Royal Society of Chemistry (RSC), 2020)
Nanotechnology can potentially revolutionize the agricultural industry by offering nano-formulations of pesticides, the so-called nano-pesticides, which can e.g. increase the efficacy and stability of the active ingredients of pesticides. However, it is unknown how a nano-formulation may modulate the interaction between the active ingredient and non-target soil (micro)organisms. Here, we show that long-term exposure to a high dosage of atrazine (ATZ) containing nano-pesticides (NPATZs), where ATZ is encapsulated in a biodegradable polymeric shell, significantly decreases the metabolic capacity of rhizosphere bacterial communities and alters their community structure and composition compared to rhizosphere bacterial communities exposed to the same amount of conventionally applied ATZ. In the rhizosphere, the NPATZs and ATZ were found to be initially degraded by Mycobacterium and Pseudomonas bacteria. As the exposure time increased, more bacterial consortia became involved in NPATZ degradation than in ATZ degradation, especially in metabolizing N-isopropylammelide to carboxybiuret catalyzed by the genes atzC and atzD. Our findings provide important insights into the time-resolved interactions between rhizosphere bacterial communities and nano-pesticides.